SP19 Gas Chronology - Epifanio, Jenna (U.S. Antarctic Program (USAP) Data Center, 2020)
We present the SP19 gas chronology for the South Pole ice core. The chronology is based on stratigraphic matching of abrupt methane (CH4) changes. To construct the chronology, abrupt changes in CH4 during the glacial period and small, 20-30ppb, centennial scale changes in CH4 were used with analogous data from the West Antarctic Ice Sheet Divide ice core. Stratigraphic matching was verified by an optimization algorithm. The ages cover the last 52,586 years. Absolute uncertainty increases with depth until ± 540 years.